Bertolt Brecht auf der Bühne nach 2000 – Skizze über die Rezeption und Bedeutung seiner Dramen in Polen - Mirecka, Agata (AUPC Studia ad Bibliothecarum Scientiam Pertinentia, 2021)
Bertolt Brecht's drama was performed frequently on Polish stages after 1945. It has often been presented and analysed in academic works. However, the aim of this article is to present the role of Bertolt Brecht's work on Polish stages today as well as to briefly outline its literary reception in Poland after the year 2000. The new productions of his plays have become a mirror of contemporary tendencies in the understanding of Bertolt Brecht's work in Poland today. The aim of the paper is to present the productions of Bertolt Brecht's plays and the publications in Poland after the year 2000. It discusses why Brecht's plays have not enjoyed such great popularity in Poland in the last 20 years. It would be a desirable basis for academic approaches and a critical discourse on Bertolt Brecht's work abroad.